KONSEP DASAR GARIS BATAS KEMUNGKINAN PRODUKSI MASYARAKAT AGRARIS SEBAGAI SUBKELOMPOK BINAAN KABUPATEN MINAHASA UTARA - Mangowal, Benny (JBE (Journal of Business and Economics); Volume 6 No.2, 2007 JBE UNKLAB, 2007)
The Production-Possibility Frontier (PPF) basically referenced as the ability to produce larger output concept in a macroeconomics’ discussion is considered related to producers’ group of the region of Minahasa Utara, as the state started to maximize its resources. In fact, as the administration tried to expand the modern economic order, the producer’s part in particular from agricultural section remain silence, as shown by the revenues they shared. Further studies mentioned that the producer’s culture mainly complied with their traditional traits in growing their life without verifying their products value.  They performed their typical plantations without considering the newly models and technologies, proposed by the well known experts of the region.  Therefore, this study begins to convince the PPF model for the administration to anticipate their future, which specified in two options or concentrations. Concentration I, for perennial-crop production (PCP).   On the other side, Concentration II the annual-crop productions (ACP).   Descriptive research was used on this study, with a qualitative designed methodology to prepare related factors for both frontier options.  This observation started with a focus group discussion in three different counties which focused the related factors for the region.   A quantitative designed then applied on the study to solve the PPF primary data.   Correlation analysis was used to observe the relationships toward factors of the study, as well as analysis of variance equation for  calculation of the differences of the variables, finally the coefficient of regression technologies were applied to specify the most related variables for recommendations.  The findings specify significantly, that annual crop productions have to be considered by the administration to anticipate for their further economic recoveries.   Annual crop technology has to be enhanced mechanically, as well as the credit facilities from banking institution have to be considered by the administration.  Access road to their side, as well as facilities for storage, and their working capital, were included as significant factors are underlined.  This study is sponsored by the Department of Education, for the Directorate of Research, No. 029/SP2H/PP/DP2M/III/Dated March the 29th 2007.